KERIS : Struktur-Fungsi-Aktivitas (Kajian dengan Pendekatan Etnoarkrologi) - Agus Irawan; Soedjijono; Ninik Indawati (Jurnal Penelitian dan Pendidikan IPS, 2021)
This study aims to understand the Keris as a historical and cultural artifact of the Indonesian nation from the perspective of Structure-Function-Activities from the past as well as the contemporary era. This research is a qualitative study, with the Ethnoarchaeological Approach to study the Keris, with the object of the Keris Artifact research collection of the Association of Society "AJISAKA" which is based at the Public Corporation. Dinoyo Permai kav. 2 Malang. Data collection methods in this study were observation, interviews and documentation. Interviews were conducted with informants namely the main board of the AJISAKA community, namely KRAP Prasena CakraAdiningrat (Chair), R. Aldo Pamalzie (Secretary), Fais Risky Amaluddin (Treasurer). The results of this study indicate that the Keris as part of the history of the Indonesian nation, has existed from around the 8th century to the present. Ancient keris as a cultural artifact, preservation while for other preservation by creating new krises. Structurally, a kris can be viewed from history, manufacture, type (dhapur), structure (materials and parts) and meaning as important for the philosophy of life. In terms of function, the kris can be seen from the cultural, social, economic and function of the kris to strengthen character education. Meanwhile, in terms of activities, the keris in terms of the use, care, preservation and community institutions around the keris